Zirconium in the Nuclear Industry: 15th International Symposium 2009
DOI: 10.1520/stp48161s
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hydride Reorientation Behavior and Mechanical Properties for High-Burnup Fuel-Cladding Tubes in Interim Dry Storage

Abstract: The hydride stress reorientation behavior and the mechanical properties of irradiated cladding tubes were investigated to evaluate the high-burnup fuel-cladding tube properties in interim dry storage. As for the boiling water reactor (BWR) Zircaloy-2 (Zry-2) cladding, the hydride reorientation to the radial direction occurred at relatively low hoop stresses during the hydride reorientation treatment (HRT), such as less than 70 MPa. The increase of reorientation with hoop stress was not monotonic for the specim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 10 publications
1
16
0
1
Order By: Relevance
“…The absence of radial hydrides is a demonstration that the hoop stress produced by inner pressure added to any other circumferential stress (if any) do not overpass the threshold to produce hydride reorientation; this is in agreement with the results obtained by Aomi et al [10]. Blisters in samples 5.5-Al-a and 5.5-Al-b were grown heating until 420°C.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The absence of radial hydrides is a demonstration that the hoop stress produced by inner pressure added to any other circumferential stress (if any) do not overpass the threshold to produce hydride reorientation; this is in agreement with the results obtained by Aomi et al [10]. Blisters in samples 5.5-Al-a and 5.5-Al-b were grown heating until 420°C.…”
Section: Resultssupporting
confidence: 89%
“…VALANCE, et al [9] reported 50 MPa for irradiated Zry-2 and 65-74 MPa for the same unirradiated material. Values above 100 MPa have been reported in Zry-4 [10] and less than 70 MPa in Zry-2 cladding of SFE [10]. Finally, the radial hydrides fraction increases inversely with cooling speed.…”
Section: Hydride Embrittlement (He)mentioning
confidence: 90%
“…In addition to the Argonne datasets for PWR cladding alloys, Aomi et al [8] have generated data for Zry-2 and Zry-4 by using test methods similar to the ones used by Argonne. However, RHT samples were cooled under constant stress (vs. decreasing stress, as used by Argonne), and RCTs were conducted only at room temperature (RT) and a slow displacement rate (0.033 vs. 5 mm/s at Argonne).…”
Section: Baseline Studies For Ring Compression Testing Of High-burnupmentioning
confidence: 99%
“…사용후핵연료의 건전성에 영향을 미칠 수 있는 요인 들로는 크립(creep) [5][6][7]과 수소화물재배열 [8][9][10], 지연수 소화균열(Delayed Hydride Cracking, DHC) [11][12][13], 응력 부식균열 [14,15], 산화 및 부식에 의한 파괴 등을 들 수 있 다 [16]. 미국 원자력안전규제위원회(U.S. Nuclear Regula- …”
Section: 서 론unclassified